Correlation of trastuzumab-based treatment with clinical characteristics and prognosis in HER2-positive gastric and gastroesophageal junction cancer: A retrospective single center analysis. Issue 3 (4th March 2018) - Ilhan-Mutlu, A.; Taghizadeh, H.; Beer, A.; Dolak, W.; Ba-Ssalamah, A.; Schoppmann, S. F.; Hejna, M.; Birner, P.; Preusser, M.
ABSTRACT: Attempts for identifying targeted therapy strategies in metastatic gastric and gastroesopheal junction cancer (upper-GI) revealed that the inhibition of human epidermal growth factor receptor-2 (HER2) by monoclonal antibody trastuzumab improves survival of these patients. Hence, adding trastuzumab to doublet chemotherapy has become the standard treatment in this setting. Although the patient survival is extended among clinical trials, the knowledge on the real-time setting is limited. With this retrospective, single center analysis of the patient data of the Medical University of Vienna, we sought to investigate the clinical characteristics and outcome of patients, who received trastuzumab-based chemotherapy for metastatic upper-GI tumor. All patients, who received trastzumab at least once were included to the analysis. Clinical and pathological data were recorded. This search revealed 33 patients. The demographic data was comparable with that of the previous clinical trials. Progression free survival (PFS) was 11 months, whereas overall survival (OS) was 21 months. OS was significantly associated with initially favorable response to treatment. Thirteen patients (39%) received trastuzumab as maintenance treatment with a median cycle number of 6. Toxicity profile was acceptable with only one patient detected to have cardiotoxicity. Taken together, trastuzumab based treatment induced a considerable PFS and OS in metastatic or advanced upper-GI tumors with acceptable toxicity profile. The maintenance therapy with trastuzumab was safe and effective in patients who had initially a favorable response to chemotherapy. The optimal duration of the maintenance therapy should be tested in future clinical trials.